Thermo-magnetic-fluid dynamics analysis of an ONAN distribution transformer cooled with mineral oil and biodegradable esters. (1st June 2021) - Garelli, L.; Ríos Rodriguez, G.A.; Kubiczek, K.; Lasek, P.; Stepien, M.; Smolka, J.; Storti, M.; Pessolani, F.; Amadei, M.
Highlights: Coupled electromagnetic and thermo-hydraulic CFD simulations of full 3-D ONAN distribution transformer. Fluid flow and heat transfer analysis for mineral oil and biodegradable natural ester. Detailed heat transfer and flow analysis inside cooling ducts of the winding. Power loss 3-D distribution in the windings and core transferred as heat source to thermofluid dynamic model. Experimental measurements of different key variables provided by transformer manufacturer. Abstract: This work introduces a coupled electromagnetic, thermal and fluid flow analysis of an oil-natural air-natural distribution transformer in order to study the changes in the heat dissipation performance when a biodegradable ester is used to cool the device instead of mineral oil. The transformer has a rated power of 315 kVA and a voltage ratio of 13.2 kV / 0.4 kV . The heat losses in the magnetic core and the windings are computed with the ANSYS® Maxwell software and they are transferred as volume heat source terms to compute the heat conduction. The natural convection of the fluid flow is taken into account using a temperature-dependent density. The heat conduction through the solid walls and radiators panels are also considered. The thermo–hydraulic problem is solved with the software Code _ Saturne . Data from experimental tests carried out with mineral oil are used to validate the numerical simulations. Equivalent and anisotropic thermal conductivities in the core and the windings are calculated both with a semi-analytic procedure and finite element simulations to simplify the heat conduction model in the active parts. It is found that, after reaching a steady state, the transformer cooled with the ester shows a temperature difference between specific locations at the top and the bottom higher than that cooled with mineral oil. The magnetic core and the windings also work hotter when ester is used. Finally, the analysis of the flow through the cooling ducts of the windings confirms that the oil velocity is, on average, 25% higher than the ester one.